The validity of using an electrocutaneous device for pain assessment in patients with cervical radiculopathy. (October 2014) - Abbott, Allan; Ghasemi-Kafash, Elaheh; Dedering, Åsa
Abstract The purpose of this study was to evaluate the validity and preference for assessing pain magnitude with electrocutaneous testing (ECT) compared to the visual analogue scale (VAS) and Borg CR10 scale in men and women with cervical radiculopathy of varying sensory phenotypes. An additional purpose was to investigate ECT sensory and pain thresholds in men and women with cervical radiculopathy of varying sensory phenotypes. This is a cross-sectional study of 34 patients with cervical radiculopathy. Scatterplots and linear regression were used to investigate bivariate relationships between ECT, VAS and Borg CR10 methods of pain magnitude measurement as well as ECT sensory and pain thresholds. The use of the ECT pain magnitude matching paradigm for patients with cervical radiculopathy with normal sensory phenotype shows good linear association with arm pain VAS (R2 = 0.39), neck pain VAS (R2 = 0.38), arm pain Borg CR10 scale (R2 = 0.50) and neck pain Borg CR10 scale (R2 = 0.49) suggesting acceptable validity of the procedure. For patients with hypoesthesia and hyperesthesia sensory phenotypes, the ECT pain magnitude matching paradigm does not show adequate linear association with rating scale methods rendering the validity of the procedure as doubtful. ECT for sensory and pain threshold investigation, however, provides a method to objectively assess global sensory function in conjunction with sensory receptor specific bedside examination measures.